A dance through time images of western social dancing from the Middle Ages to modern times - Barlow, Jeremy 1939- (Oxford Bodleian Library, University of Oxford, 2012)
Jeremy Barlow surveys over 600 years of imagery, drawing out major themes in the representation of dance. He shows how over the centuries, artists and illustrators have represented dance in a stylized and often humorous manner, with curved, flowing lines for the gracious dancer and angular postures for the uncouth, rustic, or exhibitionistic performer. He also reveals how artists have responded in imaginative ways to the challenge of how to convey a sense of the dancer's movement through a frozen moment in print, and what techniques illustrators have used to demonstrate specific poses and steps, from the galliard, mazurka, and minuet to the waltz, tango, and cha cha cha. Finally he examines the age-old tension between decorum and license on the dance floor and how this changed with the advent of jive and the untutored vitality of rock'n' roll. The book draws on a wide range of materials in the Bodleian Library, including fourteenth-century manuscripts, satirical prints, dance cards, and invitations to balls.
Keywords: Dance in art -- History; Dance in art -- Pictorial works; Dance -- History -- Pictorial works